2-Benzyloxybenzaldehyde inhibits formyl-methionyl-leucyl-phenylalanine stimulation of phospholipase D activation in rat neutrophils - Wang, Jih-Pyang; Chang, Ling-Chu; Hsu, Mei-Feng; Huang, Li-Jiau; Kuo, Sheng-Chu (Biochimica et biophysica acta, 2002)
2-Benzyloxybenzaldehyde (CCY1a) inhibited the formyl-methionyl-leucyl-phenylalanine (fMLP)-stimulated phospholipase D (PLD)-mediated products, phosphatidic acid (PA) and phosphatidylethanol (PEt) formation in rat neutrophils in a concentration-dependent manner with IC 50 values of 15.8±2.5 and 13.9±2.0 μM, respectively. The underlying cellular signaling mechanism of CCY1a inhibition was investigated. CCY1a inhibited the plateau phase but not the initial Ca 2+ spike of fMLP-stimulated Ca 2+ signal. CCY1a did not inhibit the [Ca 2+] i change in Ca 2+-free medium in response to fMLP, but inhibited the [Ca 2+] i change by the subsequent addition of Ca 2+. In addition, CCY1a treatment attenuated the fMLP-induced protein tyrosine phosphorylation. The membrane translocation of ADP-ribosylation factor (ARF) and Rho A proteins in neutrophils stimulated with fMLP was attenuated by CCY1a in a concentration-dependent manner. In a cell-free system, neither the membrane association of ARF and Rho A caused by GTPγS nor the phorbol myristate acetate-stimulated membrane translocation of Rho A was suppressed significantly by CCY1a. These results indicate that the attenuation of protein tyrosine phosphorylation, blockade of Ca 2+ entry, and the suppression of ARF and Rho A membrane translocation are probably obligatory for the CCY1a inhibition of PLD activity in rat neutrophils in response to fMLP.